Do board attributes influence Islamic social responsibility disclosure? Evidence from Indonesian sharia banking - Dessy Noor Farida; Ali Imron; Arina Rohmatika (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - This study aims to analyze further the disclosure of Islamic Social Responsibility (ISR) on board size, board independence, board diversity, and board activity.Method - This study uses quantitative methods and multiple linear regression analysis. This study uses a sample of Islamic Commercial Banks in Indonesia, which consistently reports from 2016 to 2019. The research sample is 13 Islamic Commercial Banks in Indonesia. The data analysis technique used a multiple linear regression test.Result - The results show that only board diversity can affect ISR disclosure, while the variable board size, board independence, and board activity cannot affect ISR disclosure. This study has an adjusted R square of 53.3%.Implication - This study recommends Islamic banking to increase the role of the board of directors to encourage ISR disclosure because the company's concern for social and environmental conditions can increase corporate value.Originality - In Indonesia, there are still not many researchers who have studied the attributes of the board and the disclosure of ISR. This research is expected to provide broader knowledge about the board's attributes in voluntary disclosure in the banking sector.